2021
DOI: 10.3390/biom11081176
|View full text |Cite
|
Sign up to set email alerts
|

Role of Phytonutrients in Nutrigenetics and Nutrigenomics Perspective in Curing Breast Cancer

Abstract: Breast cancer (BC) is one of the most common type of cancer and an important contributor to female mortality. Several genes and epigenetic modifications are involved in the development and progression of BC. Research in phytochemistry, nutrigenomics, and nutrigenetics has provided strong evidence that certain phytonutrients are able to modulate gene expression at transcriptional and post-transcriptional levels. Such phytonutrients may also be beneficial to prevent and treat BC. In this review, we will focus on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 137 publications
0
30
0
Order By: Relevance
“…Curcumin has been in Chinese and Hindu medicines for thousands of years, but curcumin has been an important attractor in recent decades because of its anti-cancer effect. The positive impacts of curcumin are antioxidant, anti-inflammatory, anti-proliferative, and anti-angiogenic [ 27 , 33 , 34 ]. In specific tumor cell lines and xenograft models, various curcumin experiments have been demonstrated as anticarcinogenic and therapeutic activity.…”
Section: Curcuminmentioning
confidence: 99%
“…Curcumin has been in Chinese and Hindu medicines for thousands of years, but curcumin has been an important attractor in recent decades because of its anti-cancer effect. The positive impacts of curcumin are antioxidant, anti-inflammatory, anti-proliferative, and anti-angiogenic [ 27 , 33 , 34 ]. In specific tumor cell lines and xenograft models, various curcumin experiments have been demonstrated as anticarcinogenic and therapeutic activity.…”
Section: Curcuminmentioning
confidence: 99%
“…Acute invasive fungal rhinosinusitis (AIFRS) is a potentially fatal fungal illness (Deutsch et al 2019 ) (Behl et al 2020 ) (Negru et al 2022 ). Immunocompromised patients are more vulnerable, such as those with hematological malignancies, diabetes, or organ transplantation (Hirabayashi et al 2019 ) (Bhattacharya et al 2021 ) (Mazumdar et al 2016 ). COVID-19 infected over 18 million peoples globally, 4 million in the USA, and 2 million in Bangladesh (Dong et al 2020 ) (Sindhu et al 2021a ).…”
Section: Antifungal Therapy Challenges In Covid-19-infected Patientsmentioning
confidence: 99%
“…The Lamiaceae (mint) family comprises 350 species of perennial flowering plants from the genus Scutellaria, which is endemic to Asian countries, North America, and Europe [1,2]. This genus has about 300 species, many of which can be found throughout Asia [3][4][5][6]. There are 27 Scutellaria species in Iran, 12 of which are endemic [7].…”
Section: Introductionmentioning
confidence: 99%
“…The ongoing evolution of studies on the genus Scutellaria revealed parallels and variances in its range, pharmaceutical components, phytochemical constituents, and pharmacological usage. The diversity of Scutellaria 's active substance structures and abundant biological properties suggests that illustrative associations between phytochemical analysis, phylogeny, and therapeutic implications (conventional use and advanced pharmacology) are beneficial for investigators to easily recognize the medicinal worth of this genus and investigate and exploit it [ 4 – 6 ].…”
Section: Introductionmentioning
confidence: 99%